DRUG DELIVERY SYSTEMS OF SILYMARIN - Tipparos, Wajee; Opanasopit, Praneet (Thai Bulletin of Pharmaceutical Sciences, 2017)
ซิลิมารินเป็นสารจากธรรมชาติที่สกัดได้จากต้นมิลค์ทิสเทิล (milk thistle, Silybum marianum (L.) Gaertn) ตำรับยาพื้นบ้านในทวีปยุโรปมีการนำซิลิมารินมาใช้เพื่อรักษาอาการผิดปกติของตับและถุงน้ำดี มีการศึกษาทางวิทยาศาสตร์จำนวนมากที่ยืนยันฤทธิ์ในการปกป้องตับของซิลิมาริน ซึ่งพบว่ากลไกการออกฤทธิ์นั้นมีได้หลายกลไก ได้แก่ การต้านอนุมูลอิสระ การเพิ่มเสถียรภาพของเยื่อหุ้มเซลล์ การต้านการอักเสบ การกระตุ้นการสร้างเซลล์ตับทดแทน และการยับยั้งการสร้างเส้นใยในเซลล์ตับซึ่งนำไปสู่การเกิดตับแข็งได้ เป็นต้น ซิลิมารินเป็นกลุ่มสารประกอบฟลาโวโนลิกแนนไอโซเมอร์ ประกอบด้วยซิลิบิน ร้อยละ 60-70 ซิลิคริสทิน ร้อยละ 20 ซิลิไดอะนิน ร้อยละ 10 และไอโซซิลิบินร้อยละ 5 ซิลิบินเป็นองค์ประกอบหลักของซิลิมารินและเป็นสารที่มีฤทธิ์ทางเภสัชวิทยาแรงที่สุด เมื่อให้ซิลิมารินทางการรับประทาน พบว่า ซิลิมารินจะถูกดูดซึมจากทางเดินอาหารได้เพียงร้อยละ 20 – 50 เนื่องจากมีค่าการละลายน้ำและการซึมผ่านผนังลำไส้ต่ำและถูกเมแทบอไลซ์และขับถ่ายยาออกจากร่างกายได้อย่างรวดเร็ว ส่งผลให้ชีวประสิทธิผลของซิลิมารินต่ำ ดังนั้นจึงได้นำระบบนำส่งยามาช่วยเพิ่มชีวประสิทธิผลของซิลิมาริน เช่น การกระจายซิลิมารินในสารที่สามารถละลายน้ำได้ดีด้วยวิธีโซลิดดิสเพอร์สชัน การทำให้เกิดสารประกอบเชิงซ้อนกับเบต้าไซโคลเดกซ์ทริน การทำให้เกิดสารประกอบเชิงซ้อนกับฟอสฟาทิดิลโคลีน การเตรียมในรูปแบบลิโพโซม โพรลิโพโซม นาโนพาร์ทิเคิลไขมันแข็ง ระบบนำส่งยาเกิดไมโครอิมัลชันเอง ไฮโดรเจล หรือไมเซลล์ เป็นต้น คาโอและคณะได้เตรียมตำรับยาซิลิมารินออกฤทธิ์เนิ่นเพื่อเพิ่มค่าชีวประสิทธิผลของซิลิมาริน สามารถปลดปล่อยซิลิมารินได้นานถึง 3 วัน นอกจากนี้มีการพัฒนาระบบนำส่งยาสู่เป้าหมายเพื่อเพิ่มการนำส่งซิลิมารินเข้าสู่เซลล์ตับ โดยการบรรจุซิลิมารินในตำรับลิโพโซมที่มีลิแกนด์ซิโตจีซึ่งสามารถจับกับตัวรับบนผิวเซลล์ตับได้ ดังนั้นระบบนำส่งยารูปแบบต่าง ๆ สามารถนำมาประยุกต์ใช้ในการเพิ่มชีวประสิทธิผล ควบคุมการปลดปล่อยและนำส่งซิลิมารินเข้าสู่เซลล์เป้าหมายได้ Silymarin is a natural compound extracted from milk thistle (Silybum marianum (L.) Gaertn). It has been used as a folk medicine in Europe for a long time to treat liver and gallbladder disorders. Many pieces of research have confirmed that silymarin is a hepatoprotective agent. The mechanisms of action include antioxidation, cell membrane stabilization, anti-inflammation, liver regeneration and antifibrotic effects. Silymarin consists of flavonolignan isomers, namely silybin 60-70%, silychristin 20%, silydianin 10% and isosilybin 5%. Among these isomers, silybin is the major and the most active component. However, only 20-50% of orally administered silymarin can be absorbed by the gastrointestinal tract. The therapeutic effect of silymarin is limited by its poor bioavailability due to low solubility, low permeability, extensive metabolism and rapid excretion. In order to improve the bioavailability of silymarin, drug delivery systems such as solid dispersions, complexation inclusion with beta-cyclodextrin, complexation with phosphatidylcholine, liposomes, proliposomes, solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLC), self-emulsifying drug delivery systems (SEDDS), self-microemulsifying drug delivery systems (SMEDDS), and hydrogel matrices, micelles, have been employed. Cao and coworkers prepared a silymarin 3-day release formulation to improve the oral bioavailability and develop a sustained-release formulation. Moreover, targeted delivery systems have been used to carry silymarin to target sites, especially to hepatic cells leading to induction of cellular uptake. Elmowafy and coworkers have demonstrated how to improve the delivery of silymarin to hepatic cells by loading silymarin into liposomes with hepatic targeting ligands (Sito G). In conclusion, several drug delivery systems are used for increasing bioavailability, controlling release and aiming silymarin at target sites of action.